Psychodermatology in children. A secondary analysis of the Colombian National Mental Health Survey. - Botero-Rodríguez, F.; Gómez García, L.A.; Marroquín Rivera, A.; Rincón Rodríguez, C.J.; Gómez-Restrepo, C. (European Journal of Pediatric Dermatology, 2020)
The relationship between psychiatry and dermatology has been a topic of research from a long time, because the nervous system and the skin have the same embryonic origin and are influenced by the same hormones and neurotransmitters. Additionally, the skin plays an important role in the psychodynamic development of children. The actual report is aimed at estimating the prevalence of dermatological conditions in children and describing the associations between skin and mental disorders in 7 to 11 years old children in Colombia. A secondary analysis of the data extracted from the National Mental Health Survey was carried out. This survey asked a national and regional representative sample of children aged 7 to 11 questions about mental disorder and skin problems. It was estimated that 19.9% (95%CI: [14.4,26.7] of all children presented dermatological issues. Significant differences were found between children who reside in rural areas and those whose home was located in the urban area (p=0.025). Among those with dermatitis, differences were found, revealing a larger proportion of children whose mothers consumed alcohol or psychoactive substances. Regarding mental health issues, a larger proportion of children with dermatitis presented mental disorders in the last 12 months (p=0.03), specifically anxiety disorders (p<0.001). Our study is the first to evaluate the prevalence of child dermatitis and its possible associations with mental health conditions in Colombia. The results encourage research on this potential relationship and promote subsequent robust studies. Furthermore, these results could suggest the necessity of multidisciplinary assessment of pediatric conditions.